Effects of antidepressants on body weight in patients treated in a naturalistic setting in Oman - Latifa AL-Jahwari; Mohammed Qutishat; Mandhar Almaqbali; Khalid Al Risi; Mohammed AlBreiki; Mohammed Albalushi; Salim Al-Huseini (Middle East Current Psychiatry)
Abstract Background The rising use of antidepressants is critical for managing mental health disorders, but weight gain is a concerning side effect, particularly with certain classes like TCAs and SSRIs. This study aims to investigate weight changes in Omani patients prescribed paroxetine, fluoxetine, mirtazapine, or venlafaxine. Method A cross-sectional study conducted from January to June 2023 at Sultan Qaboos University Hospital recruited adults with mental disorders on these medications. Weight measurements were taken at baseline and follow-up, with clinically significant weight gain defined as a ≥ 7% increase. Results A total of 135 participants were analyzed, showing a mean weight gain of 5.54 kg, with 60.7% experiencing significant weight gain. Mirtazapine and paroxetine exhibited the highest average weight increases (7.51 kg and 8.05 kg, respectively) compared to fluoxetine (0.69 kg) and venlafaxine (4.32 kg). No significant demographic factors influenced weight changes (p = 0.213). Conclusion The study highlights significant weight gain among Omani patients on antidepressants, particularly mirtazapine and paroxetine. This underscores the importance of monitoring weight in clinical practice and necessitates further investigations into individualized treatment strategies to manage both mental health and weight-related concerns.